Home Bias among European Students - Carlo Reggiani; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
Home bias in international trade and finance has been deeply investigated in both theoretical and applied studies. Nonetheless, we do not possess so far any experimental and/or survey assessment of the phenomenon. This paper fills this gap and examines home (and European) bias from survey data based on questionnaires handed out to university students of eleven European countries. Uneven evidence of home and European biases has been found across distinct economic decisions in some individual attitudes.
Keywords: 330